Transport mechanisms in SnO2:N, H thin film grown by chemical vapor deposition. Issue 7 (15th March 2017) - Jiang, Jie; Ostheim, Lars; Hartung, David; Lu, Yinmei; Hofmann, Detlev M.; Eickhoff, Martin; Klar, Peter J.
Abstract : Tin oxide thin films with nitrogen and hydrogen as dopants (SnO2 :N, H) were prepared by chemical vapor deposition. To investigate the charge transport mechanisms in the samples the electrical conductivities were measured in the temperature range from 280 K down to 10 K and the mechanisms were analyzed. With decreasing temperature, the dominant electrical transport processes can be well described by the sequence of band conduction, D − state conduction and nearest‐neighbor‐hopping. We also studied the effect of different nitrogen and hydrogen concentrations, originating from a variation of the NH3 flow rate in the growth process, on the charge transport mechanisms in the films.